أهمية الدعوة ومشكلاتها بماليزيا اليوم - Hafizan Muhasin (Universiti Sains Islam Malaysia, 2022)
The title of this research is " The Important of Dakwah and The Current Resistance In Malaysia". The purpose of this research is to known how far the important of da'wah in Malaysia and what is the types of resistance that occurred by 'Da'i' in the movement of da'wah. This research had been focused on the da'wah institution based on library research and personal interview. In the important of da'wah, the research had been forwarded several problems that occurred by Malaysia society till need a da'wah activities for guide them for truth way that stated by Allah and implement his order. Beside that, this research also will discuss about the types of resistance in organization of da'wah to move the Islamic da'wah either muslim or non muslim. To discuss about the resistance of da'wah, the writer also reported that the latest problem according to the research that implemented by an expert people and the experience of own 'Da'i' from the selected at da'wah institution. The finding of this research had been shown the da'wah activities couldn't separate by the Malaysian societies although have more resistances and challengers.